Agricultural Economics - Amao, Ifeoluwapo O.; Adeoye, Iyabo B. (IntechOpen, 2021)
This book discusses pertinent aspects of agricultural economics and rural development. It includes case studies that assess the impact of tomato cultivation on food security and poverty alleviation of rural dwellers and agricultural producers. Additionally, it examines farmers' knowledge of organic livestock farming, a novel method of livestock production. The book also contains a review of factors affecting the efficiency of vegetable production and the basics of good agribusiness plans for successful agribusiness activities.